Reflective practice: the essential competency for health systems and healthcare practitioners during the COVID-19 pandemic. Issue 2 (4th March 2021) - Walpola, Ramesh; Lucas, Cherie
ABSTRACT: For health systems, COVID-19 has been one of the most challenging events of the twenty-first Century requiring timely change to practices and standard operating procedures. Though pandemics have been declared in the past, the resultant public health implications of the novel virus are which no currently practising healthcare practitioner has previously experienced professionally. As such, health systems have had to rapidly adapt to changes to how health services are delivered. This article demonstrates and highlights the value of how reflective practices can be used by health systems and healthcare practitioners to create and manage meaningful change during a pandemic situation.